2004
DOI: 10.1017/s002202990400010x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E supplementation on neutrophil function, milk composition and plasmin activity in dairy cows in a commercial herd

Abstract: Fifty-six Holstein dairy cows from a commercial dairy herd in the Northern part of Greece were used to determine the effect of vitamin E supplementation on immune parameters, milk composition and milk quality. Cows were assigned to one of two experimental groups: control (no vitamin E supplementation) and vitamin E supplementation. Supplementation of vitamin E started 4 weeks prior to and continued up to 12 weeks after parturition. Supplementation included daily oral administration of vitamin E at 3000 i.u./co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 0 publications
4
52
0
3
Order By: Relevance
“…Interestingly, selenium was fed to all cows at 0.3 ppm of total dry matter. Similar results were obtained in another study that was undertaken in a commercial farm in Greece implementing oral administration of 3000 IU/cow per day starting 4 weeks before the expected day of parturition and then reduced to 1000 IU/cow per day postpartum (Politis et al, 2004). Baldi et al (2000) suggested that vitamin E supplementation (oral administration of 2000 IU/cow per day from day 14 before up to day 7 after parturition) reduces SCC by 20% to 30%, compared with the corresponding values of the control that received only 1000 IU/cow per day during the same time period.…”
Section: Vitamin E Supplementation and Milk Qualitysupporting
confidence: 85%
See 3 more Smart Citations
“…Interestingly, selenium was fed to all cows at 0.3 ppm of total dry matter. Similar results were obtained in another study that was undertaken in a commercial farm in Greece implementing oral administration of 3000 IU/cow per day starting 4 weeks before the expected day of parturition and then reduced to 1000 IU/cow per day postpartum (Politis et al, 2004). Baldi et al (2000) suggested that vitamin E supplementation (oral administration of 2000 IU/cow per day from day 14 before up to day 7 after parturition) reduces SCC by 20% to 30%, compared with the corresponding values of the control that received only 1000 IU/cow per day during the same time period.…”
Section: Vitamin E Supplementation and Milk Qualitysupporting
confidence: 85%
“…Thus, vitamin E, by affecting the expression of u-PA gene facilitates movement of neutrophils to the mammary gland during inflammation. Similar results concerning the ability of vitamin E to restore immune competency at calving were obtained by Politis et al (2004) in a trial carried out in a commercial herd in Greece using dietary supplementation (3000 IU/cow per day) from week 4 before up to week 4 after parturition. This study documents the ability of vitamin E to restore the function of neutrophils in a different environment and a less intensive management system in a country where dairy cows are likely to encounter less oxidative stress than cows in the United States of America.…”
Section: Mastitis -The Indirect Evidence (Immunity Studies)supporting
confidence: 75%
See 2 more Smart Citations
“…This effect may also have led to reduced body fat mobilisation, a finding that corresponds with the lower live weight losses observed in ewes supplemented with fish oil. Vitamin E supplementation had no main effect upon milk yield or composition and the metabolic significance of the interaction between fat source and vitamin E concentration resulting in lower milk protein production in ewes fed concentrate MB is not clear, particularly as vitamin E supplementation of lactating cattle did not affect milk protein yield in the studies of Politis et al (2004), Bell et al (2006) or Pottier et al (2006). Endogenous milk fat synthesis principally results in the secretion of short-and medium-chain fatty acids, with a significant contribution made by C 16:0 (Bauman and Griinari, 2001).…”
Section: Discussionmentioning
confidence: 98%